Different expression of GSK3β and pS9GSK3β depending on phenotype of cervical cancer: possible association of GSK3β with squamous cell carcinoma and pS9GSK3β with adenocarcinoma - Kwanghee Ahn; Sojung Kweon; Dae Woon Kim; Hojung Lee (Korean Society of Obstetrics and Gynecology, 2019)
ObjectiveThis study aimed to analyze the expression pattern of glycogen synthase kinase 3β (GSK3β) and its phosphorylated forms, GSK3β phosphorylated at Ser9 (pS9GSK3β), and GSK3β phosphorylated at Tyr216 (pY216GSK3β), in cervical squamous cell carcinoma (SCC) and adenocarcinoma (AC).MethodsWe performed immunohistochemical staining for GSK3β, pS9GSK3β, and pY216GSK3β in 64 SCC and 20 AC cases and compared their expression patterns between the 2 tumor types.ResultsIncreased GSK3β and pS9GSK3β expression but decreased pY216GSK3β expression compared with that in the normal cervix were observed in both SCC and AC specimens. Specifically, the levels of GSK3β and pS9GSK3β were significantly increased in SCC and AC, respectively. GSK3β was localized in the nucleus and/or cytoplasm of SCC and AC cells. However, pS9GSK3β was predominantly localized in the membrane of AC cells, whereas it was present in the nucleus and/or cytoplasm of SCC cells.ConclusionThe results suggest that the phosphorylation status of GSK3β changes during cervical cancer development and the different expression levels and patterns of GSK3β and pS9GSK3β are associated with the specific histologic phenotype of cervical cancer.